Moisture uptake in natural rubber via genetic algorithm: article - Abd Hamid, Nadrah; Ali, Sharif Abdulbari (2017)
This study was conducted to determine the behavior of moisture content in different shape of natural rubber and to implement the use of Genetic Algorithm on the behavior of moisture uptake in natural rubber. The time taken of water to absorb into different shapes of natural rubber and weight percentage of water absorbed inside the rubber at a given time were taken during the research. Two samples of natural rubber in rectangular and sphere shape were prepared. The dry weight of samples were taken before immersed them in water and the wet weight of sample were taken daily until the day of 21, which the equilibrium state has been reached. As a result, it has been find out that the different shape of natural rubber has affected the behavior of the natural rubber. The sphere sample has a small percentage of water absorption with value of 0.78% compared to square sample. This is due the large surface area with large volume of each unit of layer and more entry space for water to absorb completely inside the natural rubber. Thus it attained the equilibrium state faster than cube sample and it caused the low tendency of the behavior of natural rubber to change. The use of Genetic Algorithm (GA) method in this research has helped in in obtaining and displaying a result in simplest way in order to further increase the understanding of people towards the results of this research.